2020
DOI: 10.21037/gs-20-437
|View full text |Cite
|
Sign up to set email alerts
|

Mammary hamartoma: is ultrasound-guided vacuum-assisted breast biopsy sufficient for its treatment?

Abstract: Background: Mammary hamartomas were mostly benign tumors with rare rate of recurrence and malignant transformation. Ultrasound (US)-guided vacuum-assisted breast biopsy (VABB) has been reported sufficiently safe in treating many breast benign tumors but remained undefined in mammary hamartoma for its usual underdiagnosis in US. Thus, this study aims to evaluate the efficiency of US-guided VABB in treating mammary hamartomas.Methods: From May 2015 to March 2019, 3,388 lesions of 2,534 patients underwent percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, the lesion size for US-VAE may be more flexible for hamartoma. Hu et al ( 20 ) also reported that the complete excision rate for the treatment hamartoma is 96.8% (30/31) and believed that US-VAE is an alternative treatment to open surgery, especially for large mammary hamartoma. In this study, we found that US-VAE could treat fibroadenoma, adenosis, and hamartoma with great efficacy, which indicates that US-VAE is an alternative treatment to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lesion size for US-VAE may be more flexible for hamartoma. Hu et al ( 20 ) also reported that the complete excision rate for the treatment hamartoma is 96.8% (30/31) and believed that US-VAE is an alternative treatment to open surgery, especially for large mammary hamartoma. In this study, we found that US-VAE could treat fibroadenoma, adenosis, and hamartoma with great efficacy, which indicates that US-VAE is an alternative treatment to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, VABB is not without complications; to minimize the incidence of possible complications, VABB is not recommended in cases with scattered MCC, lesions close to the skin, areola and nipple complex, or chest wall due to the difficulty in access and increased risk of skin dehiscence. While Park et al reported a complication rate of 2.5% including bleeding, hematoma formation, skin injury, and dimple formation, or even pneumothorax [15], Hu et al reported pain in 22.6%, hematomas formation in 9.7%, and ecchymosis in 3.2% [16]. US-VAB is associated with a slightly higher risk of bleeding when compared to SVAB, which can be attributed to the lack of breast compression during the US-guided procedure [17].…”
Section: Discussionmentioning
confidence: 99%
“…Hamartoma is generally a benign disease but may rarely be present with breast malignancy (11,12). An excisional biopsy is usually required to differentiate a hamartoma from other benign breast lesions, such as fibroadenoma, lipoma, and cystosarcoma phyllodes (13).…”
mentioning
confidence: 99%